Strategic engagement and conversational encounter in social media - Ure, Mariano (2018)
The article approaches approach to the assumptions of methodologies for measuring online conversation. These methodologies record what users do when access to social media institutional profiles, which allows observing the impact of the publications. However, they do not take into account neither the response of institutions as a result of listening to users nor the possibilities of co-creation. Thereby, conversation is confused with mere digital interaction. Seeking for engagement is executed as a strategic action of conquest of users, which ends up stopping the advances towards a culture of collaboration. The objective is to offer a theoretical contribution that allows defining the pragmatic and ethical assumptions of both the digital interaction and the conversational encounter. With this, the conversationalist paradigm is criticized, which identifies the online linguistic exchange as the maximum degree of evolution of a social communication that pretends to achieve understanding, closeness and collaboration.